Azeotropic Behavior of the 2-Methylpropan-2-ol + water + 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide System - J. Pavlíček; G. Bogdanić; I. Wichterle (Chemical and Biochemical Engineering Quarterly, 2024)
Vapor-liquid equilibrium data were measured isothermally in the near-azeotropic region of the 2-methylpropan-2-ol + water + 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide system at 333.15, 343.15, and 353.15 K. The data were processed using a recently developed method based on a small number of experiments that provides a complete thermodynamic description of the azeotropic behavior. The parameters of the third-order Redlich-Kister equation were correlated with the ionic liquid concentration to determine an analytical dependence of both the azeotropic composition and the pressure.